Disparities in the quality of and access to services in children with autism spectrum disorders: a structural equation modeling - Mohammad Asghari Jafarabadi; Kamal Gholipour; Hassan Shahrokhi; Ayyoub Malek; Akbar Ghiasi; Hamid Pourasghari; Shabnam Iezadi (BMC, 2021)
Abstract Background Socioeconomic disparities in health and healthcare are global issues that affect both adults as well as children. Children with exceptional healthcare needs, especially those with developmental impairments, including Autism Spectrum Disorders (ASD), encounter major disparities in access to and quality of health services. However, disparities in the population of children are rarely studied. The main aim of this paper is to study the socioeconomic disparities in children with ASD by examining the association between their Social Determinants of Health (SDH) status and access to and the quality of services. Methods This is a cross-sectional study on 202 children with ASD conducted in 2019 in two provinces including Ardabil and East-Azerbaijan, in the North-West of Iran. A structured, valid questionnaire was used to collect data on demographic, SDH status, quality of services, and access to services in a population of children with ASD aged 2-16-year-old. Around 77% participants were male and the mean age of children was 2 years and 6 months. Structural Equation Modeling (SEM) were used to assess the relationship. Results Based on the results of this study, the overall mean scores of the quality of services, access to services, and SDH status were 61.23 (30.01), 65.91 (21.89), and 29.50 (22.32) out of 100, respectively. All the associations between the quality and access dimensions and quality (B: 0.464-0.704) and access (B: 0.265-0.726) scales were statistically significant (P < 0.001). By adjusting to covariates, the access was also significantly related to service quality (P = 0.004). Finally, the associations between SDH score with service quality (P = 0.039) and access (P < 0.001) were positively significant. Conclusions There are socioeconomic disparities in the quality of and access to services among children with ASD, who use ASD services, in the North-West of Iran. We recommend health/medical centers, where children are diagnosed with ASD, conducting SDH screening and providing families of low-SDH status with specific information about the quality of and access to services for children with ASD. Additionally, medical universities must have a plan to routinely monitor the quality of and access to services provided for the children with low SDH.